Hidden Threats - Mala, Faiqotul; Rahman, Fazlul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This article investigates the enduring threat of radicalism among female ex-convicts in Indonesia who, despite seeming disengagement, retain radical ideologies and reject local wisdom. It explores the complexities of their reintegration by examining how their past experiences in radical groups, through the lens of Bourdieu's concept of